Principles of taxation for business and investment planning /Sally M Jones, Shelley C Rhoades-Catanach. - Jones, Sally M.
Teaches students to recognize the role taxes play in business and investment decisions. This book presents the general role of taxation and its implications across taxpaying entities, discussing the details relevant to specific entities. It helps the students understand the framework of the tax system